2017
DOI: 10.3390/molecules22091416
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optically Active Pyrimidine Derivatives as Selective 5-HT2C Modulators

Abstract: A series of pyrimidine derivatives 4a–i were synthesized and evaluated for their binding affinities towards 5-HT2C receptors. With regard to designed molecules 4a–i, the influence of the size of alkyl ether and the absolute configuration of a stereogenic center on the 5-HT2C binding affinity and selectivity was studied. The most promising diasteromeric mixtures 4d and 4e were selected in the initial radioligand binding assay and they were further synthesized as optically active forms starting from optically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The synthesis of a series of 2,4-disubstituted pyrimidines 10 , possessing different cyclic amines, is described in Scheme 2. According to our protocol [22], we efficiently synthesized optically active 1-(3- or 4-fluorophenyl)ethan-1-ol ( R )- 16a and ( R )- 16b using an enzymatic kinetic resolution method. As per the procedure previously reported in literature [32], nucleophilic aromatic substitution (S N Ar) of 2,4-dichloropyrimidine with alcohols ( R )- 16a and ( R )- 16b selectively produced 4-alkoxypyrimidines 17a and 17b , which were subjected to an additional S N Ar reaction to afford 2-alkoxy-4-aminopyrimidines as free or N -Boc-protected amine forms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of a series of 2,4-disubstituted pyrimidines 10 , possessing different cyclic amines, is described in Scheme 2. According to our protocol [22], we efficiently synthesized optically active 1-(3- or 4-fluorophenyl)ethan-1-ol ( R )- 16a and ( R )- 16b using an enzymatic kinetic resolution method. As per the procedure previously reported in literature [32], nucleophilic aromatic substitution (S N Ar) of 2,4-dichloropyrimidine with alcohols ( R )- 16a and ( R )- 16b selectively produced 4-alkoxypyrimidines 17a and 17b , which were subjected to an additional S N Ar reaction to afford 2-alkoxy-4-aminopyrimidines as free or N -Boc-protected amine forms.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the discovery of potential 5-HT 2C agonists, the selectivity of these compounds over other 5-HT 2 subtypes is still moderate; therefore, the search for highly selective 5-HT 2C agonists remains challenging. In this regard, our group has previously reported optically active pyrimidine derivative 8 as a potent and selective 5-HT 2C agonist (Figure 2) [22]. The structure activity relationship (SAR) between related pyrimidine derivatives and 5-HT 2 subtypes revealed that a subtle change in the fluorophenylalkoxy moiety attached to pyrimidine 8 was essential to control the activation of selectivity for 5-HT 2C over 5-HT 2A and 5-HT 2B .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the radioligand assay [31,32] and surface plasmon resonance (SPR) [33], microscale-thermophoresis (MST) is another technique used to analyze the interaction between the receptor and ligand based on the thermal motion of biomolecules [34]. Human functional receptor protein (α7 nAChR) was purchased from Cloud-Clone Corp (Cloud-Clone Corp, Houston, TX, USA); this was first dissolved into a buffer solution that did not contain primary amine compounds.…”
Section: Methodsmentioning
confidence: 99%